A novel method of manual positioning based on anatomical mark (shoulder-to-shoulder) to prevent postoperative leg-length discrepancy for femoral neck fractures in hip arthroplasty - Zhang, Jin-shan; Zheng, Yong-qiang; Liu, Xiao-feng; Xu, Yong-quan; Fang, Yang-zhen; Lin, Zhen-yu; Lin, Liang; Xu, You-jia (Frontiers in Surgery, 2022)
Objective To determine whether the two lower extremities are of equal length after hip arthroplasty for femoral neck fractures, we developed a novel method of manual positioning based on anatomical mark (shoulder-to-shoulder) in hip arthroplasty. Methods Patients with femoral neck fractures requiring hip arthroplasty from July 2020 to March 2022 in the orthopedic department of Jinjiang Hospital, Fujian Province, China were recruited. Hip arthroplasty was performed using the proposed “shoulder-to-shoulder” method of manual positioning based on anatomical mark in 52 patients with femoral neck fractures who met the inclusion criteria. “Shoulder-to-shoulder” was achieved by alignment of the marked femoral “shoulder” and the “shoulder” of prosthesis stem. There were 16 male and 36 female patients, with 27 undergoing total hip arthroplasty (THA) and 25 undergoing hip hemiarthroplasty (HA). The vertical distance from the apex of the medial margin of the femoral trochanter to the tear drop line on both sides which was regarded as the length of both limbs were compared via postoperative imaging, and the apex–shoulder distance on the ipsilateral side measured via postoperative imaging was compared with those measured intraoperatively. Results All patients completed the surgery successfully. The measurement results for the lower extremities after THA were as follows: contralateral group, 43.87±5.59 mm; ipsilateral group, 44.64±5.43 mm. The measurement results for the lower extremities after HA were as follows: contralateral group, 45.18 ± 7.82 mm; ipsilateral group, 45.16 ± 6.43 mm. The measurement results for the lower extremities after all arthroplasties were as follows: contralateral group, 44.50±6.72 mm; ipsilateral group, 44.89±5.90 mm. The results for the apex–shoulder distance were as follows: postoperative imaging, 19.44±3.54 mm; intraoperative apex–shoulder distance, 27.28±2.84 mm. Statistical analysis results indicated no statistically significant difference in the postoperative bilateral lower extremity length after hip arthroplasty (P = 0.75), while a statistically significant difference was found between the intraoperative and postoperative imaging measurements of the apex–shoulder distance (P < 0.01). Conclusion The novel method of manual positioning based on anatomical mark (shoulder-to-shoulder) for femoral neck fractures in hip arthroplasty is simple and accurate, making it effective for preventing postoperative bilateral leg length discrepancy.